2021
DOI: 10.1111/jgs.17342
|View full text |Cite
|
Sign up to set email alerts
|

Design, implement, and diffuse scalable and sustainable solutions for dementia care

Abstract: Most innovations developed to reduce the burden of Alzheimer disease and other related dementias (ADRD) are difficult to implement, diffuse, and scale.The consequences of such challenges in design, implementation, and diffusion are suboptimal care and resulting harm for people living with ADRD and their caregivers. National experts identified four factors that contribute to our limited ability to implement and diffuse of evidence-based services and interventions for people living with ADRD: (1) limited market … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 28 publications
0
27
0
1
Order By: Relevance
“…UCD provides a scientifically sound, practice-based mechanism for developing mobile apps for care partners of people living with ADRD that are highly feasible and more likely to improve care partner outcomes [ 17 ]. Conversely, if apps are not designed using UCD, they are more likely to be of low quality, cause more harm than good, incur avoidable waste of financial and human resources, not provide the needed support, and compound the existing burden on care partners [ 13 , 16 , 18 - 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UCD provides a scientifically sound, practice-based mechanism for developing mobile apps for care partners of people living with ADRD that are highly feasible and more likely to improve care partner outcomes [ 17 ]. Conversely, if apps are not designed using UCD, they are more likely to be of low quality, cause more harm than good, incur avoidable waste of financial and human resources, not provide the needed support, and compound the existing burden on care partners [ 13 , 16 , 18 - 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is critical to evaluate the quality of mobile apps for ADRD care partners for several reasons [ 17 ]. First, quality assessment ensures that mobile apps produce benefits and do not have unintended health consequences for care partners or persons living with ADRD; for example, they do not increase care partner stress and burden.…”
Section: Introductionmentioning
confidence: 99%
“…Por tal razón las Naciones Unidas en 2015 (6) mencionaron que las políticas la agenda del plan de desarrollo sostenible (7) declaran que se hace pertinente promover la salud, como parte fundamental del crecimiento poblacional en condiciones socioeconómicas favorables, siendo considerable estudiar la confiabilidad científica de las escalas para medir demencia en razón de conocer sus potencialidades o debilidades (8), considerando estudiar la escala de evaluación sobre los conocimientos de la demencia (9), en razón de contrastar con la realidad latinoamericana con la intención de evidenciar fortalezas o debilidades en razón de promover mayor pertinencia en referencia al contexto socio culturalcientífico actual en contexto del Ecuador.…”
Section: Introductionunclassified
“…For example, over the past two decades numerous randomized control trials have demonstrated the effectiveness of collaborative care models for depression and dementia. Nevertheless, the probability of patients receiving these evidence-based models is very low (10)(11)(12)(13). Determinants that prevent the adoption of evidence-based practices include inconsistent internal demands, stakeholder resistance, unstable leadership, and inadequate resources (14).…”
Section: Introductionmentioning
confidence: 99%